Feeding habits of the Pacific bearded brotula Brotula clarkae Hubbs, 1944 (Ophidiidae) along the Pacific coast of Costa Rica, Central America - Naranjo Elizondo, Beatriz (2016)
The present study analyzed the diet composition, ontogenetic shifts and dietary overlap of Brotula clarkae in relation to stage of maturity and sex. Samples were collected from the trawling fishery along the Pacific coast of Costa Rica (2011–2012) at depths ranging from 41.4 to 168.3 m; however, over 80% of the sampled fish were obtained at depths between 50 and 75 m. Size ranged from 14.4 to 98.4 cm total length. Of the 323 analyzed stomachs, 44.3% were from males, 86% were from immature individuals, and 49.8% had at least one prey item. According to the prey-specific index of relative importance (PSIRI), decapod shrimps were the most important prey (57.6% PSIRIi) followed by teleosts (28.2% PSIRIi), stomatopods (10.8% PSIRIi), and crabs (3.3% PSIRIi). Male and female B. clarkae exhibited a high dietary overlap (CH = 0.94). Immature B. clarkae consumed primarily shrimps and crabs (71.5% of stomachs from immature specimens contained shrimps, which accounted for over 66.0% PSIRIi); mature individuals consumed a large proportion of teleosts and stomatopods, which together contributed to over 91.0% PSIRIi. Both immature and mature B. clarkae overlapped spatially with the commercial trawling fishery grounds along the Pacific coast of Costa Rica. However, juveniles feed predominantly on shrimps, suggesting that immature B. clarkae may be subjected to high fishing pressure as by-catch, making them particularly vulnerable to overexploitation.